2018
DOI: 10.1097/md.0000000000013586
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective observational study of micro-monovision small incision lenticule extraction (SMILE) for the correction of presbyopia and myopia

Abstract: This study was aimed to evaluate refractive and visual outcomes after micro-monovision small incision lenticule extraction (SMILE) in patients with presbyopia and myopia. In total, 72 patients (144 eyes) with a mean age of 46.0 ± 4.9 years were included in this study. The dominant eye was treated for distance vision and the nondominant eye for near vision by targeting between −0.50 and −1.75 diopters (D). Treatment efficacy, safety, and refractive stability were calculated from postoperative data including ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Studies on conventional refractive surgery using LASIK have demonstrated that 84.7% of eyes had UDVA ≥ 20/20 (Snellen lines) at 3 months postoperatively, 90.7% VA ≥ 20/40 at 0.4 m, and 86.7% overall satisfaction rate [ 12 ]. And such figures were 100% ≥ 20/32, 100% ≥ 20/40 at 0.33 m, and 86.7% of the overall satisfaction rate 1 year postoperatively using SMILE with 1.03 of the SI and 1.04 of the EI [ 13 ]. It was observed that the distant VA of the patients at the last follow-up in this study was slightly lower than that at 3 months postoperatively, as shown by the significant decrease in SE and EI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on conventional refractive surgery using LASIK have demonstrated that 84.7% of eyes had UDVA ≥ 20/20 (Snellen lines) at 3 months postoperatively, 90.7% VA ≥ 20/40 at 0.4 m, and 86.7% overall satisfaction rate [ 12 ]. And such figures were 100% ≥ 20/32, 100% ≥ 20/40 at 0.33 m, and 86.7% of the overall satisfaction rate 1 year postoperatively using SMILE with 1.03 of the SI and 1.04 of the EI [ 13 ]. It was observed that the distant VA of the patients at the last follow-up in this study was slightly lower than that at 3 months postoperatively, as shown by the significant decrease in SE and EI.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of this technique, many other applications, such as the correction of presbyopia and hyperopia, are currently in development. 3–8…”
mentioning
confidence: 99%
“…On the basis of this technique, many other applications, such as the correction of presbyopia and hyperopia, are currently in development. [3][4][5][6][7][8] As corneal refractive surgery is mostly performed in younger patients with SMILE being performed for less than 15 years now, little is known about the accuracy of intraocular lens (IOL) power calculation in eyes with previous SMILE. Regarding IOL calculation in eyes with previous SMILE, the literature is very sparse, and only single case reports can be found in the literature.…”
mentioning
confidence: 99%
“…In this pilot study, the efficacy of micro-monovision with SMILE was evaluated and binocular summation using CSDC was reported for the first time. The efficacy of micro-monovision with SMILE has been published in previous studies [ 6 , 7 , 8 ]. Unfortunately, none of these studies reported standardized VA measured in logMAR with an ETDRS chart; therefore, the efficacy of our study cannot be easily compared with previous micro-monovision studies with SMILE reporting results using non-standard methods for reporting VA, such as Jaeger notation or reading charts.…”
Section: Discussionmentioning
confidence: 99%
“…Although micro-monovision studies have been conducted with older LRS techniques such as LASIK or photorefractive keratectomy (PRK) [ 2 ], few studies have been conducted with the combination of SMILE and micro-monovision, mainly because it is a more recent technique [ 6 , 7 , 8 ]. In addition, although the usual clinical practice procedure involves the correction of distance vision in the dominant eye and near vision in the non-dominant eye [ 6 , 7 , 8 ], recent laboratory research suggests that the vision of a patient undergoing a monovision procedure may vary according to different patterns of accommodative response [ 9 ], as presbyopic patients in their 40s and 50s still retain some accommodative capabilities. Thus, depending on the accommodative response, the patient may achieve a different range of clear vision.…”
Section: Introductionmentioning
confidence: 99%